Laboratory changes and prognostic indicators of the adverse course of chronic heart failure with preserved left ventricular ejection fraction, excess weight and concomitant atrial fibrillation - P. P. Bidzilya; V. H. Kadzharian (Patologìâ)
Aim. To investigate the peculiarities of clinical and laboratory changes and to identify prognostic indicators of the adverse course of chronic heart failure with preserved left ventricular ejection fraction (CHFprEF), excess weight and concomitant atrial fibrillation (AF).